Carbon nanotube composite silver paste and preparation method thereof
By introducing dispersant into the carbon nanotube composite silver paste and mechanically processing, the problem of grid blocking of traditional silver paste during large-scale printing is solved, efficient dispersion and excellent conductivity are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411939169.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional carbon nanotube composite silver paste is blocked due to the prone to agglomeration of carbon nanotubes during large-scale printing.
By introducing a dispersant, the π-π conjugation between the carbon nanotubes is unbuttoned, so that it can be dispersed efficiently in the solvent, and the length of the carbon nanotubes is basically the same, which is lower than the number of printed screen mesh.
It effectively solves the problem of grid blocking of carbon nanotube composite silver paste during large-scale printing, improves the thixotropy and conductivity of silver paste, enhances the photoelectric conversion efficiency, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a carbon nanotube composite silver paste and a preparation method thereof. Background Art
[0002] TopCon cell is a solar cell based on the principle of selective carriers, also known as tunneling oxide passivation cell or i-TOPCon cell. Its working principle is based on the principle of selective carriers. By adding a layer of silicon dioxide on the surface of the cell, the cell can selectively pass electrons and block holes, thereby significantly improving the open circuit voltage and fill factor of the cell.
[0003] In the past decade, in the rapidly developing photovoltaic industry, high efficiency and low cost have always been the two main competitive points. Silver paste for TopCon batteries is an important basic material for making TopCon batteries. Currently, silver paste for TopCon batteries on the market basically relies on silver to carry and store electrons. Carbon nanotubes have excellent physical and chemical properties such as good stability, high strength, high specific surface area, and good electrical and thermal conductivity. They are the new type of nanocarbon material with the most development potential. Carbon nanotubes have a special tubular graphite structure and a unique ballistic electron conduction effect. Their room temperature conductivity can be as high as 10 3 S / cm. In addition, carbon nanotubes have a special one-dimensional structure, which can solve the problem of weak bonding of electrode materials. Therefore, carbon nanotubes are easy to build a complete electronic conduction network. They can be added to other conductive materials as conductive structures or conductive enhancement phases, which can significantly improve the electron and ion transmission capacity of composite materials, thereby improving the conductive properties of materials. However, traditional carbon nanotube composite silver pastes are prone to network blockage during mass printing due to the easy aggregation of carbon nanotubes.
[0004] Therefore, the industry is in urgent need of a new technology for carbon nanotube composite silver paste. Summary of the invention
[0005] The present invention aims to provide a carbon nanotube composite silver paste and a preparation method thereof, so as to solve the problem that the carbon nanotubes of the conventional carbon nanotube composite silver paste are easily agglomerated and block the screen when printing in large quantities. The introduction of a dispersant can effectively inhibit the π-π conjugation on the surface of the carbon nanotubes, so that the carbon nanotubes are efficiently dispersed, and the lengths thereof are basically consistent and lower than the mesh number of the printing screen under the treatment of pot grinding and sand grinding. At the same time, the uniform dispersion of the carbon nanotubes in the silver paste can improve the thixotropy of the silver paste, so that the silver paste can maintain an excellent aspect ratio, and the close contact between the carbon nanotubes and the silver particles can form a good conductive network, enhance the photoelectric conversion efficiency, increase the life of the photovoltaic module, and replace the silver powder content in the silver paste with the carbon nanotubes, thereby reducing the production cost.
[0006] To achieve the above object, the present invention provides a carbon nanotube composite silver paste, which comprises, by weight: 1-3 parts of carbon nanotube paste, 80-85 parts of silver powder, 1.2-2.5 parts of aluminum powder, 2-8 parts of glass powder, 7-10 parts of organic carrier, and 1-2.4 parts of a first solvent; The carbon nanotube slurry is prepared by mixing carbon nanotubes, a second solvent and a dispersant and then subjected to pot milling, sand milling and convection homogenization. The carbon nanotube slurry comprises, by weight percentage, 1-5% carbon nanotubes, 94.5-98.5% second solvent and 0.15-1.5% dispersant. Furthermore, the length of the carbon nanotubes is 2-5 microns, and the particle size of the silver powder is 0.5-2 microns.
[0007] Furthermore, the dispersant is a mixture of one or more of fatty alcohol polyoxyethylene ether sodium sulfate, sodium alkylbenzene sulfonate, polyethylene glycol octylphenyl ether, and lecithin; and the carbon nanotubes are a mixture of one or more of array carbon nanotubes, entangled carbon nanotubes, oligo-walled carbon nanotubes, and single-walled carbon nanotubes.
[0008] Furthermore, the first solvent and the second solvent are the same solvent, which are a mixture of one or more of diethylene glycol butyl ether acetate, terpineol, ethylene glycol, and dimethyl dibasic acid.
[0009] Furthermore, the organic carrier comprises, by weight percentage, 10-15% glycerol, 50-65% terpineol, 8-10% 1,4-butanediol, 10-13% epoxy resin, 1.1-2% phosphate trisaccharide, 0.2-0.5% polyamide wax, and 3.2-5.8% ethyl cellulose.
[0010] Furthermore, the glass powder comprises, by weight percentage, 4-8% aluminum oxide, 1-2% copper oxide, 3-6% lead oxide, 7-17% silicon dioxide, 60-70% barium oxide, and 3.5-9% zinc oxide.
[0011] The present invention also provides a method for preparing the above-mentioned carbon nanotube composite silver paste, comprising the following steps: S1, mixing the carbon nanotubes with the second solvent, adding a dispersant, and homogenizing by mechanical jar grinding, sand grinding, and convection to obtain a uniformly dispersed carbon nanotube slurry; S2. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and the first solvent, and pre-mix them in a homogenizer; S3, rolling the premixed slurry through a three-roller mill; S4. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer, and the viscosity is adjusted to 37-42 Pa•s, thereby obtaining a carbon nanotube composite silver paste.
[0012] Furthermore, in step S1, the solid content of the carbon nanotubes is 1%-5%, the mechanical jar mill speed is 300-600 r / min, the jar mill time is 15-20 h, the sand mill speed is 1500-1800 rpm, the sand mill time is 1-4 h, and the convection homogenization times are 3-6 times.
[0013] Furthermore, in step S2, the homogenization time in the homogenizer is 1-3 minutes, and the rotation speed is 1500-2000 rpm; in step S4, the vacuum degassing time in the homogenizer is 1-3 minutes, and the rotation speed is 1800-2300 rpm.
[0014] Furthermore, in step S3, the rotation speed of the three-roll mill is 350-390 rpm, and the fineness of the slurry after rolling is ensured to be less than 10 microns.
[0015] The present invention has the following beneficial effects: 1. The present invention provides a carbon nanotube composite silver paste, which comprises, by weight: 1-3 parts of carbon nanotube paste, 80-85 parts of silver powder, 1.2-2.5 parts of aluminum powder, 2-8 parts of glass powder, 7-10 parts of organic carrier, and 1-2.4 parts of first solvent; the carbon nanotube paste is prepared by mixing carbon nanotubes with a second solvent and a dispersant through pot grinding, sand grinding, and convection homogenization. The carbon nanotube paste comprises, by weight percentage: 1-5% carbon nanotubes, 94.5-98.5% of the second solvent, and 0.15-1.5% of the dispersant. Among them, silver powder is the main component of the conductive silver paste, which is used to provide excellent conductive properties; aluminum powder is used to enhance the corrosion resistance and reflective properties of the paste; glass powder mainly plays the role of enhancing adhesion, improving conductivity and improving sintering stability; the organic carrier is mainly used to wet and disperse silver particles, adjust the rheology and printing properties of the paste; the solvent is used to adjust the viscosity and fluidity of the paste. In addition, in order to avoid affecting the optimal sintering temperature of the slurry and causing solvent precipitation due to the carbon slurry solvent not matching the silver paste system during storage, the second solvent in the carbon nanotube slurry and the first solvent in the composite silver paste are the same solvent, so that the carbon nanotube slurry and the composite silver paste have good compatibility.
[0016] 2. The present invention provides a carbon nanotube composite silver paste, which introduces a new dispersant into the carbon nanotube paste to untie the π-π conjugation between the carbon nanotubes, so that the carbon nanotubes are efficiently dispersed in the solvent and are not easy to agglomerate. The carbon nanotube length in the paste is basically maintained at 2-5 microns under the process of pot grinding, sand grinding, convection homogenization and other processes, which is less than the mesh number of the traditional screen printing, and greatly improves the problem of the traditional carbon nanotube composite silver paste being prone to blockage during mass printing. In addition, due to the one-dimensional structure of the carbon nanotubes and the uniform dispersion of the carbon nanotubes in the silver paste, the thixotropy of the silver paste can be improved, and the excellent aspect ratio can be maintained. At the same time, the close contact between the carbon nanotubes and the silver particles can form a good conductive network, enhance the photoelectric conversion efficiency, increase the life of the photovoltaic module, and replace the silver powder content in the silver paste with carbon nanotubes, while reducing the production cost of the silver paste and ensuring the photoelectric conversion efficiency of the battery cell, and the market prospect is broad.
[0017] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention will be further described in detail below. DETAILED DESCRIPTION
[0018] The embodiments of the present invention are described in detail below.
[0019] Example 1 The carbon nanotube composite silver paste described in this example is made of the following raw materials in parts by weight: 1 part of carbon nanotube paste, 83 parts of silver powder, 1.5 parts of aluminum powder, 4.1 parts of glass powder, 8 parts of organic carrier, and 2.4 parts of solvent.
[0020] The carbon nanotube slurry described in this example includes, by weight: 1 part of oligo-walled carbon nanotubes, 97.5 parts of solvent, and 1.5 parts of dispersant.
[0021] The organic carrier described in this example includes, by weight: 13 parts of glycerol, 58 parts of terpineol, 10 parts of 1,4-butanediol, 12 parts of epoxy resin, 1.8 parts of triphosphate, 0.2 parts of polyamide wax, and 5 parts of ethyl cellulose.
[0022] The glass powder described in this example includes, by weight: 6 parts of aluminum oxide, 1 part of copper oxide, 6 parts of lead oxide, 13 parts of silicon dioxide, 65 parts of barium oxide, and 9 parts of zinc oxide.
[0023] The preparation method of the carbon nanotube composite silver paste described in this example is as follows: S1. Put the oligo-walled carbon nanotubes, solvent and dispersant into a ball mill with a ball-to-material ratio of 10:1, a mechanical mill speed of 500 r / min and a stirring time of 15 h.
[0024] S2. The carbon nanotube slurry after the pot milling treatment is subjected to sand milling treatment at a sand milling speed of 1500 rpm and a sand milling time of 4 hours.
[0025] S3, performing convection homogenization on the carbon nanotube slurry after the sand milling process, and the homogenization times are 4 times.
[0026] S4. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and solvent, and pre-mix them in a homogenizer. Set the homogenization time to 2 minutes and the speed to 1500 rpm.
[0027] S5. The premixed slurry is rolled by a three-roll mill with a rotation speed of 350 and the front and rear spacings are respectively rolled twice in the order of 60-30 μm, 40-20 μm, 20-10 μm, and 8-5 μm.
[0028] S6. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer. The homogenization and degassing time is 3 minutes and the rotation speed is 1500 rpm, thereby obtaining a carbon nanotube composite silver paste.
[0029] Example 2 The carbon nanotube composite silver paste described in this example is made of the following raw materials in parts by weight: 1 part of carbon nanotube paste, 83 parts of silver powder, 1.5 parts of aluminum powder, 4.1 parts of glass powder, 8 parts of organic carrier, and 2.4 parts of solvent.
[0030] The carbon nanotube slurry described in this example includes, by weight: 1 part of oligo-walled carbon nanotubes, 98.5 parts of solvent, and 0.5 parts of dispersant.
[0031] The organic carrier described in this example includes, by weight: 13 parts of glycerol, 58 parts of terpineol, 10 parts of 1,4-butanediol, 12 parts of epoxy resin, 1.8 parts of triphosphate, 0.2 parts of polyamide wax, and 5 parts of ethyl cellulose.
[0032] The glass powder described in this example includes, by weight: 6 parts of aluminum oxide, 1 part of copper oxide, 6 parts of lead oxide, 13 parts of silicon dioxide, 65 parts of barium oxide, and 9 parts of zinc oxide.
[0033] The preparation method of the carbon nanotube composite silver paste described in this example is as follows: S1. Put the oligo-walled carbon nanotubes, solvent and dispersant into a ball mill with a ball-to-material ratio of 10:1, a mechanical mill speed of 500 r / min and a stirring time of 15 h.
[0034] S2. The carbon nanotube slurry after the pot milling treatment is subjected to sand milling treatment at a sand milling speed of 1500 rpm and a sand milling time of 4 hours.
[0035] S3, performing convection homogenization on the carbon nanotube slurry after the sand milling process, and the homogenization times are 4 times.
[0036] S4. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and solvent, and pre-mix them in a homogenizer. Set the homogenization time to 2 minutes and the speed to 1500 rpm.
[0037] S5. The premixed slurry is rolled by a three-roll mill with a rotation speed of 350 and the front and rear spacings are respectively rolled twice in the order of 60-30 μm, 40-20 μm, 20-10 μm, and 8-5 μm.
[0038] S6. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer. The homogenization and degassing time is 3 minutes and the rotation speed is 1500 rpm, thereby obtaining a carbon nanotube composite silver paste.
[0039] Example 3 The carbon nanotube composite silver paste described in this example is made of the following raw materials in parts by weight: 1 part of carbon nanotube paste, 83 parts of silver powder, 1.5 parts of aluminum powder, 4.1 parts of glass powder, 8 parts of organic carrier, and 2.4 parts of solvent.
[0040] The carbon nanotube slurry described in this example includes, by weight: 3 parts of oligo-walled carbon nanotubes, 96.5 parts of solvent, and 0.5 parts of dispersant.
[0041] The organic carrier described in this example includes, by weight: 13 parts of glycerol, 58 parts of terpineol, 10 parts of 1,4-butanediol, 12 parts of epoxy resin, 1.8 parts of triphosphate, 0.2 parts of polyamide wax, and 5 parts of ethyl cellulose.
[0042] The glass powder described in this example includes, by weight: 6 parts of aluminum oxide, 1 part of copper oxide, 6 parts of lead oxide, 13 parts of silicon dioxide, 65 parts of barium oxide, and 9 parts of zinc oxide.
[0043] The preparation method of the carbon nanotube composite silver paste described in this example is as follows: S1. Put the oligo-walled carbon nanotubes, solvent and dispersant into a ball mill with a ball-to-material ratio of 10:1, a mechanical mill speed of 500 r / min and a stirring time of 15 h.
[0044] S2. The carbon nanotube slurry after the pot milling treatment is subjected to sand milling treatment at a sand milling speed of 1500 rpm and a sand milling time of 4 hours.
[0045] S3, performing convection homogenization on the carbon nanotube slurry after the sand milling process, and the homogenization times are 4 times.
[0046] S4. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and solvent, and pre-mix them in a homogenizer. Set the homogenization time to 2 minutes and the speed to 1500 rpm.
[0047] S5. The premixed slurry is rolled by a three-roll mill with a rotation speed of 350 and the front and rear spacings are respectively rolled twice in the order of 60-30 μm, 40-20 μm, 20-10 μm, and 8-5 μm.
[0048] S6. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer. The homogenization and degassing time is 3 minutes and the rotation speed is 1500 rpm, thereby obtaining a carbon nanotube composite silver paste.
[0049] Embodiment 4: The carbon nanotube composite silver paste described in this example is made of the following raw materials in parts by weight: 3 parts of carbon nanotube paste, 80 parts of silver powder, 2.5 parts of aluminum powder, 2.1 parts of glass powder, 10 parts of organic carrier, and 2.4 parts of solvent.
[0050] The carbon nanotube slurry described in this example includes, by weight: 2 parts of oligo-walled carbon nanotubes, 96.5 parts of solvent, and 1.5 parts of dispersant.
[0051] The organic carrier described in this example includes, by weight: 13 parts of glycerol, 58 parts of terpineol, 10 parts of 1,4-butanediol, 12 parts of epoxy resin, 1.8 parts of triphosphate, 0.2 parts of polyamide wax, and 5 parts of ethyl cellulose.
[0052] The glass powder described in this example includes, by weight: 6 parts of aluminum oxide, 1 part of copper oxide, 6 parts of lead oxide, 13 parts of silicon dioxide, 65 parts of barium oxide, and 9 parts of zinc oxide.
[0053] The preparation method of the carbon nanotube composite silver paste described in this example is as follows: S1. Put the oligo-walled carbon nanotubes, solvent and dispersant into a ball mill with a ball-to-material ratio of 10:1, a mechanical mill speed of 500 r / min and a stirring time of 15 h.
[0054] S2. The carbon nanotube slurry after the pot milling treatment is subjected to sand milling treatment at a sand milling speed of 1500 rpm and a sand milling time of 4 hours.
[0055] S3, performing convection homogenization on the carbon nanotube slurry after the sand milling process, and the homogenization times are 4 times.
[0056] S4. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and solvent, and pre-mix them in a homogenizer. Set the homogenization time to 2 minutes and the speed to 1500 rpm.
[0057] S5. The premixed slurry is rolled by a three-roll mill with a rotation speed of 350 and the front and rear spacings are respectively rolled twice in the order of 60-30 μm, 40-20 μm, 20-10 μm, and 8-5 μm.
[0058] S6. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer. The homogenization and degassing time is 3 minutes and the rotation speed is 1500 rpm, thereby obtaining a carbon nanotube composite silver paste.
[0059] Embodiment 5: The carbon nanotube composite silver paste described in this example is made of the following raw materials in parts by weight: 2 parts of carbon nanotube paste, 85 parts of silver powder, 1.2 parts of aluminum powder, 3.4 parts of glass powder, 7 parts of organic carrier, and 1.4 parts of solvent.
[0060] The carbon nanotube slurry described in this example includes, by weight: 5 parts of oligo-walled carbon nanotubes, 94.85 parts of solvent, and 0.15 parts of dispersant.
[0061] The organic carrier described in this example includes, by weight: 13 parts of glycerol, 58 parts of terpineol, 10 parts of 1,4-butanediol, 12 parts of epoxy resin, 1.8 parts of triphosphate, 0.2 parts of polyamide wax, and 5 parts of ethyl cellulose.
[0062] The glass powder described in this example includes, by weight: 6 parts of aluminum oxide, 1 part of copper oxide, 6 parts of lead oxide, 13 parts of silicon dioxide, 65 parts of barium oxide, and 9 parts of zinc oxide.
[0063] The preparation method of the carbon nanotube composite silver paste described in this example is as follows: S1. Put the oligo-walled carbon nanotubes, solvent and dispersant into a ball mill with a ball-to-material ratio of 10:1, a mechanical mill speed of 500 r / min and a stirring time of 15 h.
[0064] S2. The carbon nanotube slurry after the pot milling treatment is subjected to sand milling treatment at a sand milling speed of 1500 rpm and a sand milling time of 4 hours.
[0065] S3, performing convection homogenization on the carbon nanotube slurry after the sand milling process, and the homogenization times are 4 times.
[0066] S4. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and solvent, and pre-mix them in a homogenizer. Set the homogenization time to 2 minutes and the speed to 1500 rpm.
[0067] S5. The premixed slurry is rolled by a three-roll mill with a rotation speed of 350 and the front and rear spacings are respectively rolled twice in the order of 60-30 μm, 40-20 μm, 20-10 μm, and 8-5 μm.
[0068] S6. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer. The homogenization and degassing time is 3 minutes and the rotation speed is 1500 rpm, thereby obtaining a carbon nanotube composite silver paste.
[0069] Comparative Example 1: (without adding carbon nanotubes) The composite silver paste described in this example is made of the following raw materials in parts by weight: 84 parts of silver powder, 1.5 parts of aluminum powder, 4.1 parts of glass powder, 8 parts of organic carrier, and 2.4 parts of solvent.
[0070] The organic carrier described in this example includes, by weight: 13 parts of glycerol, 58 parts of terpineol, 10 parts of 1,4-butanediol, 12 parts of epoxy resin, 1.8 parts of triphosphate, 0.2 parts of polyamide wax, and 5 parts of ethyl cellulose.
[0071] The glass powder described in this example includes, by weight: 6 parts of aluminum oxide, 1 part of copper oxide, 6 parts of lead oxide, 13 parts of silicon dioxide, 65 parts of barium oxide, and 9 parts of zinc oxide.
[0072] S1. According to the ratio, weigh silver powder, aluminum powder, organic carrier, glass powder and solvent, and pre-mix them in a homogenizer. Set the homogenization time to 2 minutes and the speed to 1500 rpm.
[0073] S2. The premixed slurry is rolled by a three-roll mill with a rotation speed of 350 and the front and rear spacings are respectively rolled twice in the order of 60-30 μm, 40-20 μm, 20-10 μm, and 8-5 μm.
[0074] S3. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer. The homogenization and degassing time is 3 minutes and the rotation speed is 1500 rpm, thereby obtaining a comparative standard silver paste.
[0075] Comparative Example 2: (without adding dispersant) The carbon nanotube composite silver paste described in this example is made of the following raw materials in parts by weight: 1 part of carbon nanotube paste, 83 parts of silver powder, 1.5 parts of aluminum powder, 4.1 parts of glass powder, 8 parts of organic carrier, and 2.4 parts of solvent.
[0076] The carbon nanotube slurry described in this example includes, by weight: 1 part of oligo-walled carbon nanotubes and 99 parts of solvent.
[0077] The organic carrier described in this example includes, by weight: 13 parts of glycerol, 58 parts of terpineol, 10 parts of 1,4-butanediol, 12 parts of epoxy resin, 1.8 parts of trisphosphate, 0.2 parts of polyamide wax, and 5 parts of ethyl cellulose.
[0078] The glass powder described in this example includes, by weight: 6 parts of aluminum oxide, 1 part of copper oxide, 6 parts of lead oxide, 13 parts of silicon dioxide, 65 parts of barium oxide, and 9 parts of zinc oxide.
[0079] S1. Put the oligo-walled carbon nanotubes and solvent into a ball mill with a ball-to-solid ratio of 10:1, a mechanical mill speed of 500 r / min, and a stirring time of 15 h.
[0080] S2. The carbon nanotube slurry after the pot milling treatment is subjected to sand milling treatment at a sand milling speed of 1500 rpm and a sand milling time of 4 hours.
[0081] S3, performing convection homogenization on the carbon nanotube slurry after the sand milling process, and the homogenization times are 4 times.
[0082] S4. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and solvent, and pre-mix them in a homogenizer. Set the homogenization time to 2 minutes and the speed to 1500 rpm.
[0083] S5. The premixed slurry is rolled by a three-roll mill with a rotation speed of 350 and the front and rear spacings are respectively rolled twice in the order of 60-30 μm, 40-20 μm, 20-10 μm, and 8-5 μm.
[0084] S6. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer. The homogenization and degassing time is 3 minutes and the rotation speed is 1500 rpm, thereby obtaining a carbon nanotube composite silver paste.
[0085] Comparative Example 3: (Too much dispersant) The carbon nanotube composite silver paste described in this example is made of the following raw materials in parts by weight: 1 part of carbon nanotube paste, 83 parts of silver powder, 1.5 parts of aluminum powder, 4.1 parts of glass powder, 8 parts of organic carrier, and 2.4 parts of solvent.
[0086] The carbon nanotube slurry described in this example includes, by weight: 1 part of oligo-walled carbon nanotubes, 96 parts of solvent, and 3 parts of dispersant.
[0087] The organic carrier described in this example includes, by weight: 13 parts of glycerol, 58 parts of terpineol, 10 parts of 1,4-butanediol, 12 parts of epoxy resin, 1.8 parts of triphosphate, 0.2 parts of polyamide wax, and 5 parts of ethyl cellulose.
[0088] The glass powder described in this example includes, by weight: 6 parts of aluminum oxide, 1 part of copper oxide, 6 parts of lead oxide, 13 parts of silicon dioxide, 65 parts of barium oxide, and 9 parts of zinc oxide.
[0089] S1. Put the oligo-walled carbon nanotubes, solvent and dispersant into a ball mill with a ball-to-material ratio of 10:1, a mechanical mill speed of 500 r / min and a stirring time of 15 h.
[0090] S2. The carbon nanotube slurry after the pot milling treatment is subjected to sand milling treatment at a sand milling speed of 1500 rpm and a sand milling time of 4 hours.
[0091] S3, performing convection homogenization on the carbon nanotube slurry after the sand milling process, and the homogenization times are 4 times.
[0092] S4. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and solvent, and pre-mix them in a homogenizer. Set the homogenization time to 2 minutes and the speed to 1500 rpm.
[0093] S5. The premixed slurry is rolled by a three-roll mill with a rotation speed of 350 and the front and rear spacings are respectively rolled twice in the order of 60-30 μm, 40-20 μm, 20-10 μm, and 8-5 μm.
[0094] S6. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer. The homogenization and degassing time is 3 minutes and the rotation speed is 1500 rpm, thereby obtaining a carbon nanotube composite silver paste.
[0095] The composite silver pastes prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the test process was as follows: The viscosity of the slurry at 5, 10, 20, 50, 100, and 200 rpm was tested by a DV2T viscometer, and the viscosity at 100 rpm was taken as the printing reference viscosity (Table 1), and the viscosity of the carbon nanotube composite silver paste was controlled to be 39±2; second, the coating thickness was controlled to be 50μm by an automatic coater, and its square resistance was tested after low-temperature drying and high-temperature sintering processes. The test tool was an RTS-9 dual-electric four-probe tester. Third, the carbon nanotube composite silver paste was printed on a small thick film printer, and the printing specification was a line width of 30 microns without a mesh. After low-temperature drying and high-temperature sintering processes, the performance of the cell such as open circuit voltage, filling factor, photoelectric conversion efficiency, etc. was tested in the optoelectronic test system. The test results are shown in Table 1.
[0096] Table 1 As can be seen from Table 1, the conductive film and solar cell electrode obtained by the carbon nanotube composite silver paste prepared by the method of the embodiment of the present invention can effectively reduce the square resistance of the high-temperature TopCon silver-aluminum paste of the prior art, and further improve its filling factor and photoelectric conversion efficiency. Among them, Comparative Example 1 is a silver-aluminum paste, and its photoelectric efficiency is generally 23%-23.5%. On this basis, every stable increase of 0.1%~0.2% in light efficiency is a technical breakthrough. In order to avoid the impact caused by inconsistent printability, the viscosity of each slurry is controlled within the range of 40±1. As can be seen from Table 1, the silver paste of Comparative Example 1 did not block the network, while the carbon nanotube slurry of Comparative Example 2 did not add a dispersant. The agglomeration caused by the van der Waals force and the electrostatic effect between the carbon nanotubes in the carbon paste had a very obvious effect on the printability of the silver paste, so that the compounded silver paste had a network blockage within 100 times, and a large number of broken grids, resulting in a significant decrease in its photoelectric efficiency. Although there is no network blocking in Comparative Example 3, the photoelectric efficiency of Comparative Example 3 is low. This is because when the dispersant content is too high, bubbles are easily generated in the mechanical grinding process of the carbon slurry, which increases the proportion of air in the carbon slurry. If the degassing and homogenization are not performed or the degassing is incomplete after being compounded into the silver paste, small gaps may appear during the sintering process, thereby affecting and reducing its photoelectric efficiency. Therefore, the dispersant content should be controlled below 1.5 parts. The photoelectric efficiency of Example 1 and Example 2 is close. It can be seen from Example 3 that while maintaining a good dispersant ratio, the carbon nanotube content in the carbon nanotube slurry is increased to make its internal conductive network more compact, and the conductive contact between the silver particles is increased to a greater extent. Therefore, the photoelectric efficiency of the battery cell can be further improved without network blocking. The composite silver paste obtained in Example 4 and Example 5 has a similar effect to that of Example 1-3, which will not be repeated here.
[0097] In summary, the carbon nanotube composite silver paste and preparation method provided by the present invention can solve the problem that the traditional carbon nanotube composite silver paste is prone to blockage during mass printing. The mechanism lies in the aromatic hydrocarbon structure and bipolar structure of the carbon tube dispersant, which can effectively inhibit the π-π conjugation on the surface of the carbon nanotubes, and accurately control the positive and negative charge ratio on the surface of the carbon nanotubes, effectively avoiding the secondary agglomeration caused by the "salt effect", and successfully achieve efficient dispersion of carbon nanotubes, and make their length basically consistent and lower than the printing screen mesh number under the treatment of can grinding and sand grinding. Secondly, the uniform dispersion of carbon nanotubes in the silver paste can improve the thixotropy of the silver paste, so that it maintains an excellent aspect ratio. At the same time, the close contact between the carbon nanotubes and the silver particles can form a good conductive network, enhance the photoelectric conversion efficiency, increase the life of the photovoltaic module, and replace the silver powder content in the silver paste with carbon nanotubes, reducing production costs.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A carbon nanotube composite silver paste, characterized in that: The carbon nanotube composite silver paste comprises, by weight: 1-3 parts of carbon nanotube paste, 80-85 parts of silver powder, 1.2-2.5 parts of aluminum powder, 2-8 parts of glass powder, 7-10 parts of organic carrier, and 1-2.4 parts of the first solvent; The carbon nanotube slurry is prepared by mixing carbon nanotubes, a second solvent and a dispersant and then subjected to pot milling, sand milling and convection homogenization. The carbon nanotube slurry comprises, by weight percentage, 1-5% carbon nanotubes, 94.5-98.5% second solvent and 0.15-1.5% dispersant.
2. The carbon nanotube composite silver paste according to claim 1, characterized in that: The length of the carbon nanotube is 2-5 micrometers, and the particle size of the silver powder is 0.5-2 micrometers.
3. The carbon nanotube composite silver paste according to claim 1, characterized in that: The dispersant is a mixture of one or more of fatty alcohol polyoxyethylene ether sodium sulfate, sodium alkylbenzene sulfonate, polyethylene glycol octylphenyl ether, and lecithin; the carbon nanotubes are array carbon nanotubes, entangled carbon nanotubes, oligo-walled carbon nanotubes, and single-walled carbon nanotubes, or a mixture of two or more thereof.
4. The carbon nanotube composite silver paste according to claim 1, characterized in that: The first solvent and the second solvent are the same solvent, which are a mixture of one or more of diethylene glycol butyl ether acetate, terpineol, ethylene glycol, and dimethyl dibasic acid.
5. The carbon nanotube composite silver paste according to claim 1, characterized in that: The organic carrier comprises, by weight percentage, 10-15% glycerol, 50-65% terpineol, 8-10% 1,4-butanediol, 10-13% epoxy resin, 1.1-2% phosphate trisester, 0.2-0.5% polyamide wax, and 3.2-5.8% ethyl cellulose.
6. The carbon nanotube composite silver paste according to claim 1, characterized in that: The glass powder comprises, by weight percentage, 4-8% aluminum oxide, 1-2% copper oxide, 3-6% lead oxide, 7-17% silicon dioxide, 60-70% barium oxide, and 3.5-9% zinc oxide.
7. The method for preparing a carbon nanotube composite silver paste according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing the carbon nanotubes with the second solvent, adding a dispersant, and homogenizing by mechanical jar grinding, sand grinding, and convection to obtain a uniformly dispersed carbon nanotube slurry; S2. According to the ratio, weigh the carbon nanotube slurry, silver powder, aluminum powder, organic carrier, glass powder and the first solvent, and pre-mix them in a homogenizer; S3, rolling the premixed slurry through a three-roller mill; S4. The rolled slurry is subjected to vacuum homogenization and degassing treatment by a homogenizer, and the viscosity is adjusted to 37-42 Pa•s, thereby obtaining a carbon nanotube composite silver paste.
8. The method for preparing a carbon nanotube composite silver paste according to claim 7, characterized in that: In step S1, the solid content of the carbon nanotubes is 1%-5%, the mechanical jar mill speed is 300-600 r / min, the jar mill time is 15-20 h, the sand mill speed is 1500-1800 rpm, the sand mill time is 1-4 h, and the convection homogenization times are 3-6 times.
9. The method for preparing a carbon nanotube composite silver paste according to claim 7, characterized in that: In step S2, the homogenization time in the homogenizer is 1-3 minutes, and the rotation speed is 1500-2000 rpm; in step S4, the vacuum degassing time in the homogenizer is 1-3 minutes, and the rotation speed is 1800-2300 rpm.
10. The method for preparing a carbon nanotube composite silver paste according to claim 7, characterized in that: In step S3, the three-roll mill rotates at a speed of 350-390 rpm, and the slurry fineness after rolling is ensured to be less than 10 microns.
Citation Information
Patent Citations
Conductive aid for solar cell process, and conductive paste thereof
CN105845197A
Topcon front silver-aluminum paste for superfine grid screen printing and preparation method of Topcon front silver-aluminum paste
CN115831437A
Front silver-aluminum paste for N-type TOPCon solar cell and preparation method of front silver-aluminum paste
CN115910425A
Preparation method of high-dispersion carbon nanotube conductive liquid
CN116873903A
Conductive paste for forming solar cell electrode and solar cell
JP2018206530A